PERPUSTAKAAN UNIVERSITAS GADJAH MADA PENEKANAN PADA BIOCLIMATIC DESIGN DALAM KAMPUS EDUCOPOLIS - , VINCENTIUS TUTTO A, Ir. Jatmika Adi Suryabrata, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Gadjah Mada University Library should have an important role in teaching and learning process. Attraction is the main point of a Library to get attentions from students. It can be found in many ways, such as good designs, good environment, perfect collections, and complete facilities. Gadjah Mada University have a master plan, which is called Educopolis Campus, which means this principle needs all of universityâs development aspects to be required as an educating and encouraging department, for example know how to react to ecology issues. If we talk about ecology, the first thing that must cross in our mind is climate problem, which can be easily recognized nowadays. Therefore if we conclude all of the thing above, we can find a path that lead us to a design that must be ecological, climate care, in terms of architectural or non-architectural with a purpose we can attracts most of all the students to come and educating them so they purposely know how to live a good life. Without a doubt, the problem and reason of the development needs in Gadjah Mada University is about the lack of facilities in there, not just library facility, so they can not attract people to visit any of departments who need attention. If I can say in such cruel word, our facility is out of bit, so can not connect with the modernity and maturating mindset of the academy. The question is, what kind of Library do they want? Our current Library out there just fit into 90âs people. With the lifestyle and method. But for now on with bigger development of technologies, we need to improve mostly facilities of the library and the system too with a much better program. In this thesis I really want to share my ideas, my opinions, and mostly my ideology to bring in something new in the University Library, to make a good design for a better life.